ESP32 and MAX30100 with Chebyshev Filter for Enhanced Heart and Oxygen Measurement - Magfirawaty, Magfirawaty; Naval Indra Waskita; Hizkia Menahem Tandungan; Ridhan Hafizh; Syifa Jauza Suwaendi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
Health monitoring is important in the technology and information era. A health monitoring device must possess high accuracy in monitoring an individual's health. The MAX30100 sensor still exhibits low accuracy and requires improvements to enhance its precision. This study proposes a remote health monitoring system based on a MAX30100 sensor for heart rate and oxygen saturation detection. The digital signal processing method uses the Chebyshev II filter on PPG to reduce noise, and the RSA algorithm is employed to enhance data security. The results of testing the MAX30100 sensor value without a filter produced the lowest error value of 0.97%, the highest 6.59% for BPM, the lowest error value of 1.88%, and the highest error of 2.66% for SpO2. The MAX30100 sensor with the Chebyshev II filter that the author proposed has the highest level of accuracy with a low error value compared to previous tests, with the lowest error value of 0.23% and the highest 0.99% for BPM and the lowest error value of 0% and the highest error of 0.2% for SpO2. The RSA algorithm ensures secure data transmission from data modification by eavesdroppers. The average total time required by the system is 542.9 ms.